2016
DOI: 10.1002/lary.26109
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of hCLCA1 in chronic rhinosinusitis and its contribution to produce MUC5AC

Abstract: NA Laryngoscope, 126:E347-E355, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…However, the mechanism underlying MU5AC overexpression in CRS patients remains unclear. 9,31,32 As early as 1999, Voynow et al 13 proposed that HNE may increase the mRNA and protein expression of MU5AC in airway epithelial cells. Human bronchial epithelial cells and human lung cancer cells were shown to have high levels of HNE-induced MUC5AC expression.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanism underlying MU5AC overexpression in CRS patients remains unclear. 9,31,32 As early as 1999, Voynow et al 13 proposed that HNE may increase the mRNA and protein expression of MU5AC in airway epithelial cells. Human bronchial epithelial cells and human lung cancer cells were shown to have high levels of HNE-induced MUC5AC expression.…”
Section: Discussionmentioning
confidence: 99%
“…Mucus hypersecretion is major symptom in CRSwNP patients. And hyperplasia of mucous glands and increase in goblet cells are common histological changes in NP [ 1 , 2 ]. Mucins are major component responsible for mucus secretion.…”
Section: Discussionmentioning
confidence: 99%
“…And overproduction of airway mucins is an important feature, which leads to an increase in the morbidity and mortality of inflammatory respiratory diseases [ 3 , 4 ]. In the studies on mucin gene expression in NP, MUC5AC overexpression was observed in sinonasal mucosa of CRSwNP and MUC5AC was expressed 4-fold higher than MUC2 and 12-fold higher than MUC1 in NP [ 2 , 17 ]. The excessive production of MUC5AC was well known to mediated by many inflammatory mediators, cytokines, and hormones [ 16 , 18 - 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations